Superior Trunk Block: A Phrenic-sparing Alternative to the Interscalene Block. (September 2019) - Kim, David H.; Lin, Yi; Beathe, Jonathan C.; Liu, Jiabin; Oxendine, Joseph A.; Haskins, Stephen C.; Ho, Michael C.; Wetmore, Douglas S.; Allen, Answorth A.; Wilson, Lauren; Garnett, Christopher; Memtsoudis, Stavros G.
Editor's Perspective: What We Already Know about This Topic: Interscalene nerve block is commonly used for shoulder surgery for anesthesia and postoperative analgesia Unfortunately, interscalene blocks commonly result in hemidiaphragmatic paralysis What This Article Tells Us That Is New: When interscalene block was compared with superior trunk block, less frequent hemidiaphragmatic paralysis was seen in the superior trunk block group Superior trunk block was noninferior to interscalene block in terms of worst pain scores in the recovery room, and superior trunk block patients were more satisfied Background: Interscalene nerve blockade remains one of the most commonly used anesthetic and analgesic approaches for shoulder surgery. The high incidence of hemidiaphragmatic paralysis associated with the block, however, precludes its use among patients with compromised pulmonary function. To address this issue, recent studies have investigated phrenic-sparing alternatives that provide analgesia. None, however, have been able to reliably demonstrate surgical anesthesia without significant risk for hemidiaphragmatic paralysis. The utility of the superior trunk block has yet to be studied. The hypothesis was that compared with the interscalene block, the superior trunk block will provide noninferior surgical anesthesia and analgesia while sparing the phrenic nerve. Methods: This randomized controlled trial included 126 patients undergoing arthroscopic ambulatory shoulder surgery. Patients either received a superior trunk block (n = 63) or an interscalene block (n = 63). The primary outcomes were the incidence of hemidiaphragmatic paralysis and worst pain score in the recovery room. Ultrasound was used to assess for hemidiaphragmatic paralysis. Secondary outcomes included noninvasively measured parameters of respiratory function, opioid consumption, handgrip strength, adverse effects, and patient satisfaction. Results: The superior trunk group had a significantly lower incidence of hemidiaphragmatic paralysis compared with the interscalene group (3 of 62 [4.8%] vs . 45 of 63 [71.4%]; P < 0.001, adjusted odds ratio 0.02 [95% CI, 0.01, 0.07]), whereas the worst pain scores in the recovery room were noninferior (0 [0, 2] vs. 0 [0, 3]; P = 0.951). The superior trunk group were more satisfied, had unaffected respiratory parameters, and had a lower incidence of hoarseness. No difference in handgrip strength or opioid consumption were detected. Superior trunk block was associated with lower worst pain scores on postoperative day 1. Conclusions: Compared with the interscalene block, the superior trunk block provides noninferior surgical anesthesia while preserving diaphragmatic function. The superior trunk block may therefore be considered an alternative to traditional interscalene block for shoulder surgery. Abstract : When interscalene block was compared with superior trunk block, less frequent hemidiaphragmatic paralysis was seen in the superior trunk block group. Superior trunk block was noninferior to interscalene block in terms of worst pain scores in the recovery room, and superior trunk block patients were more satisfied.Supplemental Digital Content is available in the text.